Teacher’s Problems in Dealing with Autism Children in Learning Process - Maghfirah Ramadhani; Syamsul Bahri; Tgk. Maya Silviyanti (Universitas Syiah Kuala, 2020)
This research aimed at finding out the teacher’s problems in teaching English to autism children in SDLB YPAC (Sekolah Dasar Luar Biasa Yayasan Pembinaan Anak Cacat) Labui, Banda Aceh. This descriptive qualitative research was conducted by observing the classroom during the learning process and interviewing the English teacher in order to collect the data which was needed for this study. The subject of this research is an English teacher at SDLB YPAC Labui while the object of this research is the teacher’s problems in dealing with students with autism in learning process. The result of this study showed that there are there are several problems faced by the teacher in teaching students with autism namely the lack of teaching aids, hard to find visual aids that can be used to attract students’ attention, difficult to provide structured instruction of new vocabulary which is supported by visual aids, and hard to find suitable objects to encourage students’ expression. In conclusion, the main problem faced by the teacher in SDLB YPAC Labui is the lack of facility to smoothen the learning process.